Parallel Line Assignment Problems - Klein, Morton; Takamori, Hiroshi (Management Science, 1972)
Two problems involving the assignment of men to jobs, in a production system with parallel lines, to maximize the steady state system production rate are studied. In the first, in which a man's production rate is independent of the line to which he is assigned, a simple rule “group the fastest men in the same line” is shown to be optimal. In the second, in which production rates are dependent on the production line, an algorithm is developed to obtain a solution.